A comparison between conventional and digital radiography in root canal working length determination - Abesi Farida; Ehsani Maryam; Mirzapour Ali; Moudi Ehsan; Yousefi Sajad; Khafri Soraya (Wolters Kluwer Medknow Publications, 2013)
Aim and Objectives: Obtaining a correct working length is necessary for successful root canal treatment. The aim of this study was to compare conventional and digital radiography in measuring root canal working length. Materials and Methods: In this in vitro study 20 mesio buccal canal from maxillary first molars with moderate and severe curvature and 20 canal form anterior teeth with mild curvature were chosen and their working length were measured with number 15 k file (Maillefer, DENTSPLY, Germany). Then for each canal five radiographies were taken, three conventional radiographies using three methods of processing: Manual, automatic, and monobath solution; in addition to two other digital radiographies using CCD and PSP receptors. Two independent observers measured working length in each technique. Finally, the mean of working length in each group was compared with real working length using a paired T-test. Also a one-way ANOVA test was used for comparing the two groups. The level of statistical significance was P < 0.05. Results: The results have shown that there was a high interobserver agreement on the measurements of the working length in conventional and digital radiography (P≤0.001). Also there was no significant difference between conventional and digital radiography in measuring working length (P > 0.05). Conclusion: Therefore it was concluded that the accuracy of digital radiography is comparable with conventional radiography in measuring working length, so considering the advantages of the digital radiography, it can be used for working length determination.